The Poverty and Distributional Impacts of Carbon Pricing : Channels and Policy Implications - Shang, Baoping (IMF Working Papers; Working Paper, 2021)
Addressing the poverty and distributional impacts of carbon pricing reforms is critical for the success of ambitious actions in the fight against climate change. This paper uses a simple framework to systematically review the channels through which carbon pricing can potentially affect poverty and inequality. It finds that the channels differ in important ways along several dimensions. The paper also identifies several key gaps in the current literature and discusses some considerations on how policy designs could take into account the attributes of the channels in mitigating the impacts of carbon pricing reforms on households.